Adhesion Properties of Acrylonitrile-Butadiene Rubber/Standard Malaysian Rubber Blend Based Pressure-Sensitive Adhesive. (24th April 2014) - Poh, B. T.; Lamaming, J.; Tay, G. S.
Abstract : Viscosity and adhesion properties of NBR/SMR L blend based pressure-sensitive adhesive were investigated using coumarone-indene resin, toluene, and poly(ethylene terephthalate) (PET) as tackifier, solvent, and coating substrate, respectively. Coumarone-indene resin content was fixed at 40 parts per hundred parts of rubber (phr) in the adhesive formulation. The ratio of NBR/SMR L blend used was 0, 20, 40, 60, 80, and 100% of NBR content. Four different thicknesses, that is, 30, 60, 90, and 120 µm, were used to coat the PET film. The viscosity of adhesive was determined by a Brookfield viscometer, whereas loop tack, peel strength, and shear strength were measured using a Lloyd Adhesion Tester operating at 30 cm/min. Result indicates that the viscosity, loop tack, and shear strength of blend adhesives increase with % NBR. However, for peel strength, it indicates a maximum at 40% NBR blend ratio for the three modes of peel tests. In all cases, 120 µm coated sample consistently exhibits the highest adhesion values compared to the other coating thicknesses, an observation which is associated with the higher volume of adhesive in the former system.